Development of tilt, biaxiality and polar order in bent-core liquid crystals derived from 4′-hydroxybiphenyl-3-carboxylic acid - Guezeller, Dilek; Ocak, Hale; Bilgin-Eran, Belkiz; Prehm, Marko; Tschierske, Carsten (ROYAL SOC CHEMISTRY, 2015)
A homologous series of unsymmetric bent-core compounds derived from 4'-hydroxybiphenyl-3-carboxylic acid and having strongly distinct chains at both ends has been synthesized and characterized. The liquid crystalline self-assembly of the compounds was investigated by differential scanning calorimetry, optical polarizing microscopy, X-ray scattering and electro-optic methods. With increasing chain length and upon cooling a series of smectic phases was observed, starting from SmA phases having an unusual structure composed of domains with a randomized tilt direction. This is followed by a series of biaxial smectic phases, involving a smectic phase composed of tilt domains with increased size (SmCr), anticlinic and synclinic tilted smectic phases (SmCs, SmCa) and finally columnar phases with an oblique (Col(obl)) or pseudo-rectangular (Col(rec)) lattice. This phase sequence is the result of the competition between an emerging tilt, the dense packing of the bent aromatic cores leading to restricted rotation and contributing to phase biaxiality, and the steric distortion of the dense packing by the bulky 3,7-dimethyloctyloxy chains, inhibiting the formation of long range polar order. In all smectic phases the tilt is relatively small, thus providing only weak layer coupling and this provides the basis for sensitive regulatory networks determining the mode of molecular self-assembly in the resulting LC phases. The columnar phases have a tilted B-1rev-like ribbon structure with a temperature and chain length dependent inversion of the sign of birefringence. Though none of the racemic compounds show polar switching, the (S)-enantiomer of one compound shows ferroelectric-like switching in an anticlinic tilted smectic phase (SmCaPR*).
Keywords: CARBOXYL CONNECTING GROUPS; CROSS-COUPLING REACTIONS; BANANA-SHAPED MESOGENS; SMECTIC-A-PHASE; MESOPHASE BEHAVIOR; HOMOLOGOUS SERIES; NEMATIC PHASE; PHYSICAL-PROPERTIES; ACHIRAL MOLECULES; BIDENTATE LIGANDS; Materials Science; Physics